(untitled) (Bangladesh Journal of Botany, 2022)
The uniform sized corms (3.5-4.0 cm dia) of Gladiolus grandiflorus L. were dipped in various concentrations of BA (50,75, 100 and 125 mg/l) and GA3 (50 , 75 , 100 and 125 mg/l) for 24 hrs. The Membrane stability index (MSI), Relative water content (RWC), total soluble sugars and total protein content of florets increased with the increased concentrations of BA and GA3. The post harvest quality parameters also improved with BA and GA3 treatments as compared to control but GA3 had more significant effect than BA. The treatment with 125 mg/l GA3 significantly hastened the opening of basal floret, increased the floret size, number of florets open at one time, per cent of opening of florets, water absorbed and led to maximum reduction in pH that ultimately led to improvement in vase life. Bangladesh J. Bot. 51(2): 297-304, 2022 (June)